Methods for assessing the economic efficiency of implementing AI–based chatbots for customer experience management - E. V. Mishchenko; M. I. Yarantseva; D. N. Verzhykovskyi; S. A. Ghazaryan (Путеводитель предпринимателя, 2025)
This study focuses on identifying the place, role, and specific features of enhancing the economic efficiency of implementing and using chatbots in customer experience management.   The purpose of the study is to summarize the theoretical aspects of chatbot use in managing customer experience and to analyze the methods for assessing the economic efficiency of investments in such technologies.   The paper presents the concept and characteristics of chatbots and clarifies the variety of chatbot types available to businesses, highlighting the relevance of developing efficiency assessment methods. The strengths and weaknesses of chatbot use, along with opportunities and threats in customer experience management, are identified. The specific features of AI–based chatbots in customer experience management are formulated. The functional differences and the need for chatbot intellectualization are emphasized. Various methodologies for evaluating the effectiveness of chatbot implementation are summarized and compared. The paper conceptually justifies the necessity of considering not only economic efficiency but also the functional and goal–oriented alignment of the technology, which broadens the understanding of comparative analysis approaches for different chatbot configurations and other digital marketing tools.